Prevalence and Risk Factors of Intestinal Parasitic Helminths among Primary School Children in Oru West Lga, Imo State, Nigeria - Onwuka Chigozie Divine (Journal of Parasite Research, 2025)
Intestinal parasitic helminths pose a significant public health burden, particularly among children. This cross-sectional study investigated the prevalence and risk factors of intestinal parasitic helminths among 550 school children aged 4-12 years in Oru-West L.G.A, Imo State, Nigeria. Stool samples were examined using parasitological techniques, and questionnaires were administered to collect data on risk factors. The overall prevalence of intestinal parasitic helminths was 49.1% (270/550), with Ascaris lumbricoides being the most prevalent (30.37%). Multivariate analysis revealed significant associations between intestinal parasitic helminths and lack of hand-washing, insufficient toilet facilities, consumption of unwashed vegetables, and poor environmental sanitation. Males had a significantly higher infection rate than females (P < 0.05). Age-related prevalence was highest among children aged 4-6 (51.85%). Occupational status and educational level of parents were also significant predictors of infection. These findings highlight the need for public health education, provision of basic sanitation facilities, and regular de-worming as preventive measures.
Keywords: intestinal parasitic helminths